S‐Adenosyl‐S‐carboxymethyl‐L‐homocysteine: a novel cofactor found in the putative tRNA‐modifying enzyme CmoA. (21st May 2013) - Byrne, Robert T.; Whelan, Fiona; Aller, Pierre; Bird, Louise E.; Dowle, Adam; Lobley, Carina M. C.; Reddivari, Yamini; Nettleship, Joanne E.; Owens, Raymond J.; Antson, Alfred A.; Waterman, David G.
<x xml:space="preserve">Abstract</x> Uridine at position 34 of bacterial transfer RNAs is commonly modified to uridine‐5‐oxyacetic acid (cmo5U) to increase the decoding capacity. The protein CmoA is involved in the formation of cmo5U and was annotated as an S‐adenosyl‐L‐methionine‐dependent (SAM‐dependent) methyltransferase on the basis of its sequence homology to other SAM‐containing enzymes. However, both the crystal structure of Escherichia coli CmoA at 1.73 Å resolution and mass spectrometry demonstrate that it contains a novel cofactor, S‐adenosyl‐S‐carboxymethyl‐L‐homocysteine (SCM‐SAH), in which the donor methyl group is substituted by a carboxymethyl group. The carboxyl moiety forms a salt‐bridge interaction with Arg199 that is conserved in a large group of CmoA‐related proteins but is not conserved in other SAM‐containing enzymes. This raises the possibility that a number of enzymes that have previously been annotated as SAM‐dependent are in fact SCM‐SAH‐dependent. Indeed, inspection of electron density for one such enzyme with known X‐ray structure, PDB entry 1im8, suggests that the active site contains SCM‐SAH and not SAM.